COMMUNITY STRUCTURE OF ECHINODERMATA IN THE SEAGRASS HABITAT OF SANUR BEACH, BALI - Cika Syalomita Simbolon; I Wayan Arthana; Ni Luh Gede Rai Ayu Saraswati (NETIZEN: JOURNAL OF SOCIETY AND BUSSINESS, 2025)
This study aims to analyze the community structure of Echinodermata and its relationship with the seagrass ecosystem at the study site. Echinodermata are an important group of organisms in the seagrass ecosystem because they act as nutrient recyclers and detritus feeders, helping maintain ecosystem balance. The study was conducted using the quadrat transect method, observing the types and abundance of Echinodermata as well as seagrass cover, while also measuring water quality parameters such as temperature, salinity, and dissolved oxygen (DO). The results showed the presence of several species of Echinodermata, with diversity and dominance varying between stations. In addition, a positive relationship was found between the abundance of Echinodermata and seagrass cover as well as water quality, indicating that healthy and high-quality seagrass beds support a more abundant and diverse Echinodermata community. This study emphasizes the importance of conserving and managing seagrass ecosystems as habitats and sources of livelihood for Echinodermata and for maintaining the ecological functions of coastal areas.